(3GdeWdY Ydi eSGFd GdebfYs - (3eMeO Hf SYjO Hf eMeO Hf jMji GdShSi GdeQZJis; (3eMeO Hf SYjO Hf eMeO Hf jMji GdShSj GdeQZJj,J (B1090 (3g` s ((3eMeO Hf Hhce eMfU Hf OGd s)
(3ChdgG (B:s
(3GdMeO ddg MeOkG cKjQkG WjHkG eHGQckG ajg hHYO agPG JbjjO eNJUQ Ydi fXei GdeSei HGdebfY HYO eG cfJ bHd gPG hVYJ Ydjg TQMkG WhjdkG h ef CQGO GdWhjd GdcKjQ aYdjg HTQMfG GdcHjQ GdeSei (B: (3GdeeJY ai TQM GdebfY s
(3BNQgG (B:s
(3bO GfJgi GdeNJUQ GdebUhO hQHfG dGZjQg GdeMehO CYfi gPG GdeNJUQ GdPi SejJg Ci jbfY bGQFg hjcajg ai Yde GdfXe GdefShH ddTjN CHj GdeaRY hCHjGJ gPG GdeNJUQ hgj JSYI hJSYhf HjJkG , eGFI EdG hGMOkG GfJgi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdfXe ajgG HGdMeQI s
(3fSNI bOjeI JGeI eUMMI s
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMQha h GdChaGbs